ChemInform Abstract: Pd(OAc)2‐Catalyzed Macrocyclization of 1, 2‐Diazonaphthoquinones with Cyclic Ethers. Issue 36 (9th September 2014) - Kitamura, Mitsuru; Kisanuki, Masato; Kanemura, Koichi; Okauchi, Tatsuo
Abstract The reaction of (Ic) with (II) does not yield the corresponding cyclization product, but a dimer via linkage of the two diazo groups.